Investigation of effect from low-energy plasma immersion ion bombardment of extracellular DNA and gene fragment on mutation induction - C. Jaichuen (2018)
This study was aimed to investigate relevant aspects of effect from low-energy plasma ion bombardment of DNA on mutation induction for fundamental understanding of low-energy ion effect on life. Samples of extracellular plasmid DNA pUC19 and DNA fragment containing lacZ gene were directly bombarded using the nitrogen plasma immersion ion implantation (PIII) method with varied bias in an order of kV and varied fluences in an order of 1015ions/cm2. The PIII-treated DNA and DNA fragment were transformed using the electroporation into bacteria Escherichia coli (E. coli) to observe mutation induction. Mutant DNA was sequenced. The mutation frequencies as a function of the bias voltage at a fixed fluence and as a function of the fluence at a fixed bias were found to increase linearly as increasing of the bias or the fluence. Damage in the lacZ gene was thereafter identified to be responsible for the bacterial mutation induced by PIII of DNA. DNA sequencing confirmed the lacZ gene damage and revealed the damage types dominated by the base substitution and cytosine having the highest radiation-sensitivity. © 2012 Elsevier B.V.